ORGANIZATION OF REPORTING IN AGILE PROCESSES: REQUIREMENTS, SOLUTIONS AND CHALLENGES - Horshchar, Kateryna (European Journal of Interdisciplinary Issues, 2025)
The article examines the features of reporting organizations in Agile processes with a focus on software quality assurance (QA). Reporting requirements, modern tool solutions and methodological approaches that promote transparency, effective communication and product quality maintenance in a dynamic Agile environment are analyzed. Key categories of stakeholders are considered – project managers, developers, business representatives and QA teams – and their information needs that require adaptation of formats and periodicity of reports. An author’s model of reporting organization is proposed, which integrates automation through CI/CD pipelines, adaptability of report formats to the needs of different audiences and transparency of processes through the use of monitoring systems such as Prometheus and Grafana. The strategic importance of differentiated reporting is justified in terms of the rapid implementation of sound decisions, helping to increase trust in the quality control team and developing a quality culture in the organization. The tools mentioned in this part with special attention are Allure, TestRail, Zephyr, Jenkins, GitHub Actions and GitLab CI, which help automate, visualize data, and predict quality risks using analytics and artificial intelligence. The study focuses on a flexible reporting system that takes into account the specifics of the project, its scale, and stakeholder requirements, as well as integrating with new technologies for processing large amounts of information. The proposed model creates a single reporting ecosystem that helps synchronize the efforts of all project participants, increases the efficiency of Agile processes, and supports the achievement of business goals. Challenges such as excessive bureaucracy or insufficient digital communication in distributed teams are overcome through a structured approach to identifying needs and using automated tools. The study results provide practical recommendations for implementing effective reporting that promotes transparency, efficiency, and quality in Agile development.